2015
DOI: 10.1002/fsn3.262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermentation time on the functional and pasting properties of defatted Moringa oleifera seed flour

Abstract: Effects of fermentation time on the functional and pasting properties of defatted Moringa oleifera seed flour was examined. Moringa seeds were fermented naturally at 0, 12, 24, 48 and 72 h; oven dried at 60°C for 12 h; milled into five different flour samples for each fermentation time and defatted. The functional and pasting properties of the samples were determined. The result shows significant increase in the water absorption capacity, oil absorption capacity, foaming capacity and emulsifying capacity with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 21 publications
4
47
1
3
Order By: Relevance
“…The low BD values of the FQD show its ability to support heating and shear stress (Adebowale, Adeyemi, & Oshodi, ). Nevertheless, Oloyede et al () and Pranoto et al () found that BD values increased in fermented food, which demonstrates that each type of starch exhibits different behaviors when subjected to fermentation processes.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The low BD values of the FQD show its ability to support heating and shear stress (Adebowale, Adeyemi, & Oshodi, ). Nevertheless, Oloyede et al () and Pranoto et al () found that BD values increased in fermented food, which demonstrates that each type of starch exhibits different behaviors when subjected to fermentation processes.…”
Section: Resultsmentioning
confidence: 98%
“…For both inoculum concentrations, the FV increased as the fermentation process proceeded, and there was a decrease on day 4. Some reports have shown that this behavior is due to the breakdown of complex carbohydrates within the starch granules, allowing the leaching of amylose and subsequent SB or by the action of proteolytic enzymes, which release starches from the protein matrix (Oloyede, James, Ocheme, Chinma, & Akpa, ; Pranoto et al, ). Meanwhile, a decrease in the FV value was induced by starch molecule depolymerization because they are in contact with the metabolites of LAB, such as organic acids (Costa, Garcia, Ribeiro, Junior, & Caliari, ; Dias, Elias, Oliveira, & Helbig, ; Hirashima, Takahashi, & Nishinari, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oloyede, James, Ocheme, Chinma, and Akpa () showed that 71‐hr natural fermentation of defatted M. oleifera seed flour increased significantly the WAC (0.86–2.31 g/ml), oil absorption capacity (0.87–1.91 g/ml), foaming capacity (9.76%–16.31%), and emulsifying capacity (50.71%–68.75%). Concomitantly, natural fermentation induced a significant decrease in bulk density (0.53–0.32 g/cm 3 ) and dispersibility (36.00%–20.50%).…”
Section: Functional Properties Of Moringa Oleifera Seedsmentioning
confidence: 99%
“…The studies have shown that flour with low PV has a lower thickening power than flour with high PV. The increase in viscosity of fermented buckwheat flour might be due to the BD of complex carbohydrates to simple sugars [11]. The HPV ranged from 36 cp for cooked buckwheat flour to 1203 cp for fermented buckwheat flour.…”
Section: Pasting Propertiesmentioning
confidence: 99%